Analysis of Defamation on the X Account of Gibran Rakabuming Raka - Muhammad Ieduddien; Teguh Setiawan (Britain International for Academic Research (BIAR) Publisher, 2026)
This study examines the practice of defamation in the comment section of Gibran Rakabuming Raka’s social media account on X during the period from December 2023 to February 2024. A qualitative method was employed using reading and note-taking techniques, alongside theoretical triangulation combining Defamation Theory and Syntax Theory to ensure data validity. Data analysis was conducted using equivalence (padan) and distribution (agih) methods. The findings reveal that the linguistic forms of defamation consist of words (57 instances), phrases (82 instances), clauses (56 instances), and sentences (8 instances), with phrases and words dominating as concise yet sharply meaningful expressions. In terms of defamation types, insults (142 instances), defamation of character (38 instances), slander (22 instances), and blasphemy (1 instance) were identified, with insults being the most prevalent form. These findings indicate that defamation on social media tends to be direct, brief, and targets both the personal image and public reputation of the subject.